The Impact of Professional Portfolio on Nurses Clinical Competence - Masoud Bahreini; Fazlollah Ahmadi; Shohre Shahamat; Soodabeh Behzadi (Kerman University of Medical Sciences, 2012)
Background & Objectives: Portfolios as new educational tools can play an important role in improving clinical competence of nurses However scientific evidences about the impact of portfolios on nurses clinical competence are limited and few studies have been done in Iran This study aimed to determine the impact of professional portfolio on nurses clinical competence in a hospital affiliated to Shiraz University of Medical Sciences Methods: In this quasiexperimental pretest intervention posttest study from 22 units of the selected hospital 4 general units were selected randomly Nurses of 2 units were studied as experimental group and participated in a 12month portfoliobased Professional development program Nurses of 2 other units were considered as control group and participated in the routine professional development programs of their units Data were collected by a valid and reliable scale measuring clinical competence of nurses Data were analyzed by using descriptive statistics independent and paired ttest Results : After intervention mean clinical competence in experimental group showed a significant increase from 7672 (± 645) to 8568 (± 643) (p